Searching dark photons using displaced vertices at Belle II - with backgrounds - Jaeckel, Joerg; Phan, Anh Vu (Journal of high energy physics, 2024)
Dark photons in the MeV to GeV range with kinetic mixing of the order of ≲ 10−4 − 10−3 can be produced in significant numbers at low energy colliders such as Belle II. Their decay length can be macroscopic raising the hope for a fairly clean search via displaced vertices as proposed in [1]. However, even this is not background free. Here, we calculate and discuss problematic backgrounds from displaced photon conversion and discuss their potential impact on the sensitivity. In addition we also briefly consider the dangers of prompt backgrounds.